Atrial fibrillation is not associated with altered left atrial microRNA expression profile in ischemic end-stage human heart failure. (25th November 2020) - Ruppert, M; Agg, B; Sayour, A.A; Kugler, S.Z; Perge, P; Daroczi, L; Polos, M; Benke, K; Ferdinandy, P; Merkely, B; Radovits, T
Abstract: Introduction: In patients with chronic heart failure (CHF) left ventricular dysfunction results in elevated left atrial (LA) pressure, triggering pathological atrial remodelling and atrial fibrillation (AF). Nevertheless, it has been reported that some patients with CHF remain in sinus rhythm (SR) despite of the pathological structural alterations (e.g. dilation and fibrosis) of the LA. Of particular interest, data is scarce regarding the molecular explanation for the observed variability in AF development among CHF patients. Recent studies have indicated that alterations in microRNA (miRNA) expression might contribute to the pathogenesis of AF. However, the majority of previous studies focusing on miRNA expression compared healthy LA with SR to pathologically remodelled, dilated LA with AF. Consequently, whether dysregulation of miRNA expression directly contribute to AF and not only to pathological LA remodelling has not been tested before. Purpose: The present study aimed to investigate miRNA expression in comparably remodelled LA from end-stage CHF patients with permanent AF (CHF-AF) or SR (CHF-SR). Methods: LA samples were collected from male, non-diabetic, ischemic end-stage CHF patients undergoing heart transplantation (n=24). Patients were carefully selected to avoid any differences in age (55±2 vs. 54±2 years, CHF-AF vs. CHF-SR, n.s.), ejection fraction ([EF]: 22.5±1.8 vs. 23.3±2.5%, CHF-AF vs. CHF-SR, n.s.) LA diameters (longitudinal LA diameter: 56±4 vs. 48±5mm.; CHF-AF vs. CHF-SR, n.s.; horizontal LA diameter: 61±2 vs. 54±3, CHF-AF vs. CHF-SR, n.s.) and NYHA stage. As a molecular marker of atrial load, the mRNA expression of atrial natriuretic peptide (ANP) was measured with qRT-PCR. The extent of left atrial fibrosis was assessed on picrosirius red stained histological sections. Global LA miRNA expression profiling (including the measurement of 800 human miRNA) was carried out using a commercially available kit. Results: LA mRNA expression of ANP was comparable between the AF-CHF and the SR-CHF groups, suggesting that atrial load occurred to the same level in the two experimental groups. Furthermore, no differences could be observed in the extent of atrial collagen content between the AF-CHF and the SR-CHF groups (collagen area: 20.3±1.3% vs. 23.9±3.1%, n.s.), providing evidence that fibrotic remodelling had occurred to a similar magnitude. The high-throughput miRNA measurement revealed no differences in atrial miRNA expression between the two study groups. Conclusion: The present study provides evidence for the first time that AF is not associated with different LA miRNA expression in end-stage CHF patients with comparable level of LA dilatation, ANP expression (atrial load) and interstitial fibrosis. Based on these findings, the potential of miRNA-based therapeutic interventions might be limited in AF patients with ischemic end-stage CHF. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): NVKP_16-1-2016-0017